Does age matter?: a MRI study on peritumoral edema in newly diagnosed primary glioblastoma - Seidel, Clemens; Dörner, Nils Kristofer; Osswald, Matthias; Wick, Antje; Platten, Michael; Bendszus, Martin; Wick, Wolfgang (BMC cancer, 2011)
Peritumoral edema is a characteristic feature of malignant glioma related to the extent of neovascularisation and to vascular endothelial growth factor (VEGF) expression.
Gesehen am 31.10.2022